Flat foot at 5 to 6-year-old and history of delayed walking - Gilbert Sterling Octavius; Thalia Sugiarto; Fransisca Handy; Rima Natasha Hartanto (Indonesian Pediatric Society, 2020)
Background Flat foot, also known as pes planus, is a common problem in daily pediatric practice. For most children, this physiologic condition gradually disappears with age. However, flat foot that persists after the age of four might have developmental coordination disorder in the future and it may relate to the history of delayed walking . Objective To determine the prevalence of delayed walking in children with pes planus compared to children with normal foot curvature and to assess for a possible association between flat foot and history of delayed walking. Methods This cross-sectional study was done in 120 children aged 5-6 years. Foot curvature was evaluated by wet footprint test. Inclusion criteria include children in 3 playgroups in Tangerang from January to August 2018, in children aged 5-6 years. Children with history of neurologic diseases, genetic disorders, chronic diseases, disorders of the lower extremities except pes planus, and obesity were excluded. Grading of pes planus refers to Olivier et al. criteria and evaluation of delayed walking at 18-month-old was done through history taking from their parents. Results Of 120 children, 41 (34.2%) had pes planus while 11 (9.2%) had a history of delayed walking. Of those 11 children, 9 had pes planus. Most children with pes planus had grade I (78%). There was a significant association between pes planus and delayed walking (OR=10.8; 95%CI 2.2 to 52,9; P=0.001;). Conclusion In 5-6-year-old children, there is a significant association between pes planus grade 2 & 3 and history of delayed walking early in life. Wet footprint test screening for children with a history or signs of delayed walking may be used to identify pes planus in order to implement treatment in a timely manner.